2020
DOI: 10.1186/s12938-020-0759-6
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of miR-153 ameliorates ischemia/reperfusion-induced cardiomyocytes apoptosis by regulating Nrf2/HO-1 signaling in rats

Abstract: Background Previous in vitro studies demonstrated that suppression of microRNAs might protect cardiomyocytes and neurons against oxygen–glucose deprivation and reoxygenation (OGD/R)-induced cell apoptosis. However, whether the protective effect of miR-153-inhibition on cardiomyocytes can be observed in the animal model is unknown. We aimed to address this question using a rat model of ischemia–reperfusion (I/R). Methods Rats were received the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…However, HMOX1 can also promote ferroptosis in cancer cells in therapeutic contexts [22]. There is also prior evidence that HMOX1 primarily plays a bene cial role in IR injury [23]. Pei et al demonstrated that normobaric hyperoxia can promote HMOX1 upregulation, thereby protecting against renal IR injury [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, HMOX1 can also promote ferroptosis in cancer cells in therapeutic contexts [22]. There is also prior evidence that HMOX1 primarily plays a bene cial role in IR injury [23]. Pei et al demonstrated that normobaric hyperoxia can promote HMOX1 upregulation, thereby protecting against renal IR injury [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, attenuating ROS overproduction in reoxygenation with the antioxidant N-acetyl cysteine (NAC) suppressed Nrf2 activation, pointing to ROS as signaling mediators of Nrf2. Along the same line, activation of the Nrf2 pathway by miRNAs protects rat and mouse cardiomyocytes against in vitro IR or oxygen and glucose deprivation (OGD) followed by reperfusion [ 114 , 115 , 116 ]. We have shown that Nrf2 expression is elevated during reperfusion in isolated perfused mouse hearts (Langendorff system) [ 117 ].…”
Section: Role Of Nrf2 In Ischemia–reperfusion Injurymentioning
confidence: 99%
“…Several miRNAs modulate IR injury by regulating the Nrf2 pathway (reviewed in [ 122 , 123 , 124 ]). Thus, upregulation of miRNA-153 inhibits Nrf2/heme oxygenase-1 and induces ROS production and apoptosis in cardiomyocytes after OGD followed by reoxygenation [ 115 ] and in a rat model of IR [ 116 ]. Overexpression of miR-210 in cardiomyocytes reduces ROS production and cell death, while downregulation of miR-210 increases ROS levels after hypoxia/reoxygenation [ 125 ].…”
Section: Role Of Nrf2 In Ischemia–reperfusion Injurymentioning
confidence: 99%
“…For example, the inhibition of miR-148b-3p protected neurons against OGD/R-induced apoptosis and ROS production by enhancing Sestrin2/Nrf2 antioxidant signaling [ 177 ]. Inhibition of miR-153 ameliorated ischemia reperfusion-induced cardiomyocyte apoptosis by regulating the Nrf2/HO-1 signaling pathway in rats [ 178 ]. Interestingly, dietary compounds have the potential to control atherosclerosis by targeting miR-155 to activate the Nrf2 pathway [ 179 ].…”
Section: Clinical Prospects Of Targeting Nrf2 For Preventing Ccvdmentioning
confidence: 99%